KATP channel blockers control glucagon secretion by distinct mechanisms: A direct stimulation of α-cells involving a [Ca2+]c rise and an indirect inhibition mediated by somatostatin - Bilal Singh; Firas Khattab; Heeyoung Chae; Lieven Desmet; Pedro L. Herrera; Patrick Gilon (Elsevier, 2021)
Objective: Glucagon is secreted by pancreatic α-cells in response to hypoglycemia and its hyperglycemic effect helps to restore normal blood glucose. Insulin and somatostatin (SST) secretions from β- and δ-cells, respectively, are stimulated by glucose by mechanisms involving an inhibition of their ATP-sensitive K+ (KATP) channels, leading to an increase in [Ca2+]c that triggers exocytosis. Drugs that close KATP channels, such as sulfonylureas, are used to stimulate insulin release in type 2 diabetic patients. α-cells also express KATP channels. However, the mechanisms by which sulfonylureas control glucagon secretion are still largely debated and were addressed in the present study. In particular, we studied the effects of KATP channel blockers on α-cell [Ca2+]c and glucagon secretion in the presence of a low (1 mM) or a high (15 mM) glucose concentration and evaluated the role of SST in these effects. Methods: Using a transgenic mouse model expressing the Ca2+-sensitive fluorescent protein, GCaMP6f, specifically in α-cells, we measured [Ca2+]c in α-cells either dispersed or within whole islets (by confocal microscopy). By measuring [Ca2+]c in α-cells within islets and glucagon secretion using the same perifusion protocols, we tested whether glucagon secretion correlated with changes in [Ca2+]c in response to sulfonylureas. We studied the role of SST in the effects of sulfonylureas using multiple approaches including genetic ablation of SST, or application of SST-14 and SST receptor antagonists. Results: Application of the sulfonylureas, tolbutamide, or gliclazide, to a medium containing 1 mM or 15 mM glucose increased [Ca2+]c in α-cells by a direct effect as in β-cells. At low glucose, sulfonylureas inhibited glucagon secretion of islets despite the rise in α-cell [Ca2+]c that they triggered. This glucagonostatic effect was indirect and attributed to SST because, in the islets of SST-knockout mice, sulfonylureas induced a stimulation of glucagon secretion which correlated with an increase in α-cell [Ca2+]c. Experiments with exogenous SST-14 and SST receptor antagonists indicated that the glucagonostatic effect of sulfonylureas mainly resulted from an inhibition of the efficacy of cytosolic Ca2+ on exocytosis. Although SST-14 was also able to inhibit glucagon secretion by decreasing α-cell [Ca2+]c, no decrease in [Ca2+]c occurred during sulfonylurea application because it was largely counterbalanced by the direct stimulatory effect of these drugs on α-cell [Ca2+]c. At high glucose, i.e., in conditions where glucagon release was already low, sulfonylureas stimulated glucagon secretion because their direct stimulatory effect on α-cells exceeded the indirect effect by SST. Our results also indicated that, unexpectedly, SST-14 poorly decreased the efficacy of Ca2+ on exocytosis in β-cells. Conclusions: Sulfonylureas exert two opposite actions on α-cells: a direct stimulation as in β-cells and an indirect inhibition by SST. This suggests that any alteration of SST paracrine influence, as described in diabetes, will modify the effect of sulfonylureas on glucagon release. In addition, we suggest that δ-cells inhibit α-cells more efficiently than β-cells.